2021
DOI: 10.35762/aer.2021.43.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Formation Potential of Ambient Volatile Organic Compounds at Roadside in Bangkok, Thailand

Abstract: Volatile organic compounds (VOCs) play an important role in atmospheric chemistry due to their high reactivity—reacting photochemically with oxides of nitrogen (NOx) in the presence of solar radiation forming tropospheric ozone (O3). Each VOC species have different effects on ozone formation according to the rates and pathways of their reactions. The objective of this study aims to examine ozone formation from the estimation of ozone formation potential (OFP). The observation of 29 VOCs species was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In Bangkok, traffic and open burning of biomass are the main sources of particulate matter [6,43]. O 3 is a secondary gas formed in the air through interactions between nitrogen oxides (NOx) and volatile organic compounds (VOCs) under the influence of solar radiation [55]. Previous research conducted in Bangkok has indicated that O 3 has health impacts and still occurs at a high level [56,57].…”
Section: Excess Risk Of Mortalitymentioning
confidence: 99%
“…In Bangkok, traffic and open burning of biomass are the main sources of particulate matter [6,43]. O 3 is a secondary gas formed in the air through interactions between nitrogen oxides (NOx) and volatile organic compounds (VOCs) under the influence of solar radiation [55]. Previous research conducted in Bangkok has indicated that O 3 has health impacts and still occurs at a high level [56,57].…”
Section: Excess Risk Of Mortalitymentioning
confidence: 99%
“…Northeast Thailand has several important sources of VOCs. Vehicle exhaust represents a significant source of VOC emissions in urban areas [18,19]. In particular, the incomplete combustion of motorbikes, which are a popular mode of transportation in the area, can create high ambient concentrations of VOCs [20].…”
Section: Introductionmentioning
confidence: 99%